Respuesta :
Answer:
x=-16/3 (-5.33)
Step-by-step explanation:
3(x-2)+4x=10(x+1)
3x-6+4x=10x+10
7x-6=10x+10
-6-10=10x-7x
-16=3x
x=-16/3
Answer: [tex]x=-\frac{16}{3}[/tex]
Step-by-step explanation:
Given the equation [tex]3(x - 2) + 4x = 10(x+ 1)[/tex], you need to solve for the variable "x":
Apply Distributive property:
[tex]3x - 6 + 4x = 10x +10[/tex]
Add the like terms:
[tex]7x - 6= 10x+10[/tex]
Subtract 10 to both sides of the equation:
[tex]7x - 6-10= 10x +10-10\\\\7x-16=10x[/tex]
Subtract [tex]7x[/tex] from both sides:
[tex]7x-16-7x=10x-7x\\\\-16=3x[/tex]
And finally divide both sides by 3:
[tex]\frac{-16}{3}=\frac{3x}{3}\\\\x=-\frac{16}{3}[/tex]